Effect of variable air flow on the energy efficiency of a centralized combustion air system - Marrero-Ramírez, Secundino (2023)
The research analyzes how manual control in the combustion air system in furnaces of a metallurgical plant can generate energy overconsumption, by using the throttling of a damper with the use of manipulated valves to manually regulate the air flow. Where the system’s centrifugal fans work all the time at full capacity and this produces electrical energy losses, due to the system’s operating dynamics. The demand of the system is variable and its programming is difficult, for this reason an alternative was evaluated that consists of controlling the activation of the fans through variable speed drives with an integral proportional control loop that allows establishing the air flow through non-direct measurement of airflow, using variable pressure to achieve a 30% reduction in power demand with the control system.